Ethics in human research: a review in articles published in Paulista Journal of Physical Education - Tenório, Maria Cecília Marinho; Bezerra, Jorge; Tassitano, Rafael Miranda; Barros, Mauro Virgílio Gomes De; Costa, Aurélio Molina Da (Brazilian journal of physical education and sport, 2005)
With the publication of the Resolution 196/96 of the Brazilian National Health Council, all research projects must observe the ethical principles of autonomy, non-maleficence, beneficence, and justice. Ethical Committees are responsible for observing the procedures used in the development of studies and periodicals must incorporate the resolution in their publication guidelines. The objective of this study was to analyze the contents of original manuscripts published in the Paulista Journal of Physical Education in light of their observance of the ethical principles in human subject research. All articles published between 1996 and 2004 were analyzed. Each article was evaluated along the following dimensions: study outline and ethical questions. The analyses included descriptive statistics procedures and exploratory analysis. There was mention of a guarantee of anonymity in only two studies, while five articles mentioned the signature of a term of free and informed consent. Only two articles made express reference to the Ethical Committees approval of the study. No article mentioned all three safeguards. Though the Paulista Journal of Physical Education submission guidelines suggest that authors include references to the subjects’ consent, only a small number contained that information. It is suggested revision of the publication norms of the Paulista Journal of Physical Education, showing more incisively the necessity of information of ethical aspects in the body of the manuscript.